A Comprehensive Literature Review on the Role of Networking Skills in Enhancing Graduate Employability - Chantrea, Moeurn (LPPI Yayasan Almahmudi bin Dahlan, 2026)
The Cambodian Skills Roadmap is tasked with developing the country’s workforce into highly skilled, productive human capital capable of meeting current and future market requirements. Simultaneously, networking skills are becoming increasingly essential in the knowledge economy, leading to a corresponding increase in the skills required for graduate employability. The effect of employee networking competency on employability will be investigated in this paper. The objective of this paper is to investigate the pivotal role of networking skills in augmenting graduate employability. The article employs secondary sources, including official documents, books, journals, reports, and websites, to support its arguments. Thematic analysis is then employed to facilitate the organization and extraction of meaningful insights from the complex information presented. The review reveals that networking skills offer three primary advantages: developing skills and knowledge, achieving career success, and personal branding and lifelong learning. In the face of uncertain future career prospects, it is highly advisable to cultivate networking skills through the utilization of effective communication platforms.